Determinants of bank technical efficiency: A South African study - Abels, Jared (Department of Finance and Tax, 2021)
The purpose of this study is to investigate the determinants of technical efficiency, using data envelopment analysis and the Tobit regression model, of the six largest listed South African banks for the years 2008-2018. An input-oriented intermediary constant-return-to-scale approach was followed to determine technical efficiency scores. After technical efficiency scores were obtained, a binary data set was created by assigning a score of 1 to all observations that were regarded as technical efficient, whereas all observations that were regarded as technically inefficient were assigned a score of 0. Thereafter, a Tobit regression analysis was performed to test the following hypotheses: skimping hypothesis, diversification hypothesis, bad management hypothesis and the funding hypothesis. The results of the regression analysis show that the skimping, diversification, and bad management hypotheses were not relevant for the six largest South African banks over the period under review. Regression results pointed towards the funding hypothesis being applicable to the six largest listed banks over the review period. It can therefore be suggested that the banks under review were generally well managed with a keen focus on expense control and thorough underwriting. To ensure the efficiency of large listed banks, it is proposed that regulators continue to monitor large banks as evidence of the study suggests that as deposit bases grow, a deterioration in technical efficiency is experienced. Generally, the results of the study indicate that the six large listed banks are overall relatively efficient over the review period.